Synthesis of Silicate Nanoporous and Its Grafting with Amine and Metal Ligands for the Removal of Cr(VI) in Industry and Environment - Ghasem Zolfaghari; Abolfazl Zanganeh Asadabadi (محیط زیست و مهندسی آب)
The carcinogenicity and high toxicity of chromium (VI) show that the removal of this pollutant in industry, water resources, and the environment is necessary. Nanoporous materials have a high ability to remove pollutants. The aim of this study was to synthesize SBA-16 nanostructure using P123 and F127 surfactants and TEOS precursor and grafting its surface in two steps with -NH2 (NH2-SBA-16) and then with copper (Cu-NH2-SBA -16). Cu-NH2-SBA-16 was identified as a new adsorbent by XRD, SEM, EDX, and FT-IR analysis. The synthesis of nanoporous functionalized with amino group -NH2 was done by reflux and then grafting of prepared nanoporous with copper (II) solution was performed. The maximum adsorption capacity of NH2-SBA-16 and Cu-NH2-SBA-16 was 6.66 and 34.48 mg/g, respectively. In addition, the kinetics of chromium adsorption followed the pseudo-second-order kinetic model. The maximum efficiency of chromium removal by Cu-NH2-SBA-16 for contact time, initial concentration, amount of adsorbent, pH and temperature were 15 min, 10 mg/l, 1 g/l, 2, and 25 °C, respectively; adsorption capacity of Cu-NH2-SBA-16 increased after the modification process. The synthesized nanoadsorbent with an efficiency of 90% had a spontaneous and endothermic adsorption process, and its adsorption capacity did not decrease significantly after 3 regenerations.